The Role of Financial Literacy and Digital Innovation in Enhancing SME Performance - Rini, Asrini; Kurniawan, Kurniawan; Salida, Amrizal; Haeril, Haeril; Fatra, Emil (Newinera Publisher, 2025)
This study investigates how Financial Literacy and Digital Innovation contribute to the performance of Micro, Small, and Medium Enterprises (MSMEs). It fills a gap in empirical research concerning the effects of financial literacy and digital innovation on MSME growth. A conceptual framework grounded in agency theory has been established. The research involved distributing 200 questionnaires to MSME stakeholders in Sidenreng Rappang District, South Sulawesi. Data was gathered through surveys and analyzed using multiple regression to evaluate the influence and interaction of these two factors on MSME performance. Hypotheses were tested via multiple linear regression to assess how independent variables affect the dependent variable. The results show that both financial literacy and digital innovation have a significant individual impact on MSME performance. Moreover, the interaction of financial literacy and digital innovation also positively influences MSME performance. These findings are anticipated to offer valuable insights for policymakers in crafting programs that enhance MSME growth through improved financial literacy and digital innovation. Additionally, academics can further contribute to the advancement of new theories and knowledge in this area.Keywords: Financial Literacy, Digital Innovation, SME Performance.